Peran Pemerintah Desa dalam Pelayanan Administrasi Masyarakat di Desa Gantarang: Peran Pemerintah Desa dalam Pelayanan Administrasi Masyarakat di Desa Gantarang - Reski Astuti; Salman Salman; Muhammad Takdir (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study analyzes the role of village government in administrative services to the community in Gantarang Village, Sinjai Tengah District, Sinjai Regency. The research uses a qualitative descriptive approach through interviews, direct observation, and document review. The analytical focus covers the village organizational structure, service standard operating procedures, types and volume of administrative services, service-user records, archive management, and citizen complaints. The findings indicate that the village government performs service, regulatory, coordination, and facilitation roles through document reception, verification, letter issuance, and assistance to residents. Administrative services are supported by organizational structure, outgoing-letter records, service registers, and several standard letter formats. However, service certainty remains constrained by incomplete written procedures, limited service-information boards, manual archive systems, irregular monthly recapitulation, and undocumented complaint handling. The study recommends simple service SOPs, visible requirement lists, monthly register recapitulation, archive standardization, and a documented complaint mechanism. These improvements are essential to strengthen administrative accountability, service transparency, and public trust at the village level